Pengembangan Media Interaktif Berbasis STEM untuk Meningkatkan Literasi Ekonomi dan Literasi Lingkungan Siswa SMA - Vebrina, Dinda; Siregar, Nurul Husna; Siregar, Hotmaida Lestari (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to develop an interactive learning media based on the STEM (Science, Technology, Engineering, and Mathematics) approach to enhance students’ economic and environmental literacy at the secondary school level. The research employed a Research and Development (R&D) method using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subjects were 30 tenth-grade students from SMA Negeri 1 Angkola Selatan. The instruments used included expert validation sheets, pre-test and post-test questionnaires, and student response questionnaires. The validation results indicated that the media was categorized as highly feasible with an average score of 91.5%. The student trial showed that 86% of the students found the media very helpful, and 14% found it helpful in understanding the learning materials. The effectiveness test showed a significant improvement in students' economic and environmental literacy scores, with an average pre-test score of 62 and a post-test score of 85. The N-Gain value of 0.61 indicated a moderate to high level of effectiveness. This media proved to be academically effective and socially relevant, as it supports contextual learning, critical thinking, and awareness of environmental sustainability. Therefore, the STEM-based interactive media is feasible to be used as an interdisciplinary learning alternative under the Merdeka Curriculum.